Promoting Islam through research and publication: theses and journals - El-Mesawi, Mohamed El-Tahir (IIUM Press, 2013)
Theses and journals are key indicators for academic achievement of a University. Analyzing these academic output assists in assessing and evaluating not merely the quality of students' researches but also the productivity level of supervisors and the contributions made by the faculties and departments of the University. It would also help in identifying research trends and monitoring research and publication activities. The purpose of the present research work is to provide an overall view of International Islamic University Malaysia, IIUM academic output as manifested in Master and Ph. D. dissertations produced by the University students in the different postgraduate programmes as well as the refereed journals that are published the University through its different Kulliyyahs and Institutes and Centres. Therefore, concerning the first component, the chapter will cover a long time span since the first postgraduate programme was launched. This requires comprehensive statistical data that will be classified and compared according to different criteria, including years, Kulliyyahs, levels (MA/Ph.D.), specializations, etc. As for journals, similar but not identical criteria will be applied. The end result of the chapter shall consist in providing as accurately as possible a general picture of the volume of academic products in these two respects, without however delving into any analysis of their specific contents, as this will require time and efforts that the immediate purpose of the University commemorative book does not allow for. As such, the chapter will map out the University’s academic output in terms of dissertations and journals, thus paving the ground for any future thematic and in-depth analysis and critical evaluation of its contents. Keywords: IIUM, academic output, research, scholarship, students, dissertations, journals, publication.